Client Proteins and Small Molecule Inhibitors Display Distinct Binding Preferences for Constitutive and Stress-Induced HSP90 Isoforms and Their Conformationally Restricted Mutants. - Thomas L Prince; Toshiki Kijima; Manabu Tatokoro; Sunmin Lee; Shinji Tsutsumi; Kendrick Yim; Candy Rivas; Sylvia Alarcon; Harvey Schwartz; Kofi Khamit-Kush; Bradley T Scroggins; Kristin Beebe; et al. (PLoS ONE)
The two cytosolic/nuclear isoforms of the molecular chaperone HSP90, stress-inducible HSP90α and constitutively expressed HSP90β, fold, assemble and maintain the three-dimensional structure of numerous client proteins. Because many HSP90 clients are important in cancer, several HSP90 inhibitors have been evaluated in the clinic. However, little is known concerning possible unique isoform or conformational preferences of either individual HSP90 clients or inhibitors. In this report, we compare the relative interaction strength of both HSP90α and HSP90β with the transcription factors HSF1 and HIF1α, the kinases ERBB2 and MET, the E3-ubiquitin ligases KEAP1 and RHOBTB2, and the HSP90 inhibitors geldanamycin and ganetespib. We observed unexpected differences in relative client and drug preferences for the two HSP90 isoforms, with HSP90α binding each client protein with greater apparent affinity compared to HSP90β, while HSP90β bound each inhibitor with greater relative interaction strength compared to HSP90α. Stable HSP90 interaction was associated with reduced client activity. Using a defined set of HSP90 conformational mutants, we found that some clients interact strongly with a single, ATP-stabilized HSP90 conformation, only transiently populated during the dynamic HSP90 chaperone cycle, while other clients interact equally with multiple HSP90 conformations. These data suggest different functional requirements among HSP90 clientele that, for some clients, are likely to be ATP-independent. Lastly, the two inhibitors examined, although sharing the same binding site, were differentially able to access distinct HSP90 conformational states.